Stem Cell Based Therapy for Skeletal Muscle Diseases - Bhagavati, Satyakam (Current Stem Cell Research & Therapy, 2008)
The use of stem cells to repair and replace damaged skeletal muscle cells in chronic, debilitating muscle diseases such as the muscular dystrophies holds great promise. Different stem cell populations, both of embryonic and adult origin display the potential to generate skeletal muscle cells and have been studied in animal models of muscular dystrophy. These include muscle derived satellite cells; bone marrow derived mesenchymal stem cells, muscle or bone marrow side population cells, circulating CD133+ cells and cells derived from blood vessel walls such as mesoangioblasts or pericytes. The design of effective stem cell based therapies requires a detailed understanding of the molecules and signaling pathways which determine myogenic lineage commitment and differentiation. We discuss the great strides that have been made in delineating these pathways and how a better understanding of muscle stem cell biology has the potential to lead to more effective stem cell based therapies for skeletal muscle regeneration for devastating muscle diseases.
Keywords: mesoangioblasts